(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Corporate Social Responsibility (CSR) has evolved into a critical aspect of modern business, encompassing a company’s commitment to ethical practices, social well-being, and environmental sustainability. This paper examines the intersection of CSR initiatives and the legal obligations of companies